Navigating the Energy Maze The Transition to a Sustainable Future - Kuhns, Roger James (Springer International Publishing, 2018)
This book presents essential information for the development of a comprehensive sustainable energy policy. It examines the diverse types of energy, their resource abundance and the material needs to develop and use them, and how communities and cities can better control their own destinies by locally managing energy use and generation. This approach does not suggest the undoing of existing infrastructures and energy providers, but rather a cooperative transition from national-regional energy management to a more local-centered system. The information is the foundation for eight specific legislative initiatives necessary for a national comprehensive sustainable policy that can both facilitate and drive the process of evolution from a carbon-energy economy to a sustainable renewable energy future.